Pain, depression, and quality of life in neuromyelitis optica spectrum disorder: a cross-sectional study of 166 AQP4 antibody-seropositive patients - Ayzenberg, Ilya; Richter, Daniel; Henke, Eugenia; Asseyer, Susanna; Paul, Friedemann; Trebst, Corinna; Hümmert, Martin W.; Havla, Joachim; Kümpfel, Tania; Ringelstein, Marius; Aktaş, Orhan; Wildemann, Brigitte; et al. (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2021)
Objectives To evaluate prevalence, clinical characteristics, and predictors of pain, depression, and their impact on the quality of life (QoL) in a large neuromyelitis optica spectrum disorder (NMOSD) cohort. - Methods We included 166 patients with aquaporin-4-seropositive NMOSD from 13 tertiary referral centers. Patients received questionnaires on demographic and clinical characteristics, PainDetect, short form of Brief Pain Inventory, Beck Depression Inventory-II, and Short Form 36 Health Survey. - Results One hundred twenty-five (75.3%) patients suffered from chronic NMOSD-associated pain. Of these, 65.9% had neuropathic pain, 68.8% reported spasticity-associated pain and 26.4% painful tonic spasms. Number of previous myelitis attacks (OR = 1.27, p = 0.018) and involved upper thoracic segments (OR = 1.31, p = 0.018) were the only predictive factors for chronic pain. The latter was specifically associated with spasticity-associated pain (OR = 1.36, p = 0.002). More than a third (39.8%) suffered from depression, which was moderate to severe in 51.5%. Pain severity (OR = 1.81, p < 0.001) and especially neuropathic character (OR = 3.44, p < 0.001) were associated with depression. Pain severity and walking impairment explained 53.9% of the physical QoL variability, while depression and walking impairment 39.7% of the mental QoL variability. No specific medication was given to 70.6% of patients with moderate or severe depression and 42.5% of those with neuropathic pain. Two-thirds (64.2%) of patients with symptomatic treatment still reported moderate to severe pain. - Conclusions Myelitis episodes involving upper thoracic segments are main drivers of pain in NMOSD. Although pain intensity was lower than in previous studies, pain and depression remain undertreated and strongly affect QoL. Interventional studies on targeted treatment strategies for pain are urgently needed in NMOSD.